ALGORITMA FP-GROWTH UNTUK MENGANALISA POLA PEMBELIAN OLEH-OLEH - Bunda, Yola Permata (Riau Journal Of Computer Science, 2020)
Ummi Aufa Judge Center is one of the companies that provide typical souvenirs of West Sumatra. Visitors who come are guests from outside of West Sumatra, the time given guide for shopping is very limited, and the placement of goods in the store is not in accordance with consumer behavior in buying goods simultaneously in one time. This study aims to increase sales at the Center By-By Ummi Aufa Hakim. The data to be processed in this study is taken from invoice sales transaction. Data is processed by the Association Rule Â method using FP-Growth Algorithm, for testing results done with applications that have been designed using MySQL PHP programming language. The results of the test obtained the Association Rule s of products purchased simultaneously in one time, ie if you buy 250g Yellow Whisk, then buy Sj. Balado Redah 250gr with 20% support value and Confidence value 100%, if buy Ganepo 250gr, then buy Sj. Red Balado with 20% support value and Confidence 100% value, and if buy Krk. Small Kaliang 250gr, then buy Sj. Balado Redah 250gr with 20% support and Confidence 100%. From the test results can be seen that the application of data mining using FP-Growth Algorithm can be used to analyze consumer shopping patterns, and can be a recommendation in the layout of the product on the preparation rack. So the products are often purchased simultaneously placed adjacent by the store